New Median Approach to Define Configuration Weakness of Deformation Networks - Hekimoglu, Serif; Erdogan, Bahattin (ASCE-AMER SOC CIVIL ENGINEERS, 2012)
The main problem in conventional deformation analysis (CDA) is that if there is more than one displaced point in a given monitoring network, the least-squares estimation (LSE) smears the disturbing effects of the displaced points over all other points. Therefore, only one displaced point can be detected successfully using CDA. If the number of displaced points increases, the success of detecting these points decreases significantly. This weakness of CDA originates mostly from the configuration of the monitoring network. To detect the weakness of any monitoring network, a new approach that is based on applying the median of differences between the measurements of Epoch I and Epoch II related to the same point has been developed. In this way, the displaced points that are detected by CDA can be checked whether these points are actually displaced from the point of view of the configuration weakness of the network. To design a capable deformation network that has at least a minimum configuration isolating smearing effect of LSE makes it possible to detect displaced points with highest success. DOI: 10.1061/(ASCE)SU.1943-5428.0000080. (C) 2012 American Society of Civil Engineers.
Keywords: Monitoring networks; Configuration weakness; Deformation analysis; Median; ROBUSTNESS; Engineering